2022
DOI: 10.3389/fcvm.2022.878199
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant SERPINs: Endogenous Regulators of Hemostasis and Thrombosis

Abstract: Appropriate activation of coagulation requires a balance between procoagulant and anticoagulant proteins in blood. Loss in this balance leads to hemorrhage and thrombosis. A number of endogenous anticoagulant proteins, such as antithrombin and heparin cofactor II, are members of the serine protease inhibitor (SERPIN) family. These SERPIN anticoagulants function by forming irreversible inhibitory complexes with target coagulation proteases. Mutations in SERPIN family members, such as antithrombin, can cause her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 268 publications
(307 reference statements)
0
24
0
Order By: Relevance
“…The balance, i.e., homeostasis of the coagulation-fibrinolysis system, is based on a delicate balance between proteases. In addition, the negative control of coagulation and fibrinolysis is exercised through protease inhibitors, such as serin protease inhibitors (SERPINs) [ 113 ]. Anticoagulant SERPINs include antithrombin, heparin cofactor II, protein Z-dependent protease inhibitors (ZPI), protease nexin 1, and the C1-inhibitor.…”
Section: Homeostasis Of Hemostasismentioning
confidence: 99%
“…The balance, i.e., homeostasis of the coagulation-fibrinolysis system, is based on a delicate balance between proteases. In addition, the negative control of coagulation and fibrinolysis is exercised through protease inhibitors, such as serin protease inhibitors (SERPINs) [ 113 ]. Anticoagulant SERPINs include antithrombin, heparin cofactor II, protein Z-dependent protease inhibitors (ZPI), protease nexin 1, and the C1-inhibitor.…”
Section: Homeostasis Of Hemostasismentioning
confidence: 99%
“…4 C1INH is a potent inhibitor of plasma kallikrein, which spans the kallikrein kinin pathway and intrinsic coagulation pathway, and the intrinsic coagulation pathway components activated FXII and activated factor XI. 4,5 Consistent with the function of C1INH as a critical negative regulator of the intrinsic coagulation pathway, patients with HAE in remission have significantly increased plasma levels of the coagulation biomarkers prothrombin fragment 1 + 2, thrombin-antithrombin (TAT) complexes, and Ddimer compared to healthy controls. [6][7][8] The plasma level of these coagulation biomarkers are further increased in HAE patients during acute attacks compared to HAE patients in remission.…”
Section: Hereditary Angioedema Is Associated With An Increased Risk O...mentioning
confidence: 87%
“…Modeling analysis of the AT protein revealed that the mutated AT protein lost its domain when interacting with FIXa. Heparin-binding AT action involves two distinct mechanisms: allosteric activation and bridging [64,65]. Among these, FIXa and FXa are the main target proteases that are rapidly inhibited by heparin through the allosteric activation of AT [66,67].…”
Section: Discussionmentioning
confidence: 99%